PENGARUH COSOL VENT POLAR PADA KELARUTAN β-KAROTIN DALAM CO2 SUPERKRITIK - J P Sitompul; H Wahyudi; I N Widiasa; A Suwono (Mesin, 1997)
A simple correlation and prediction of β-carotene in supercritical CO2 involving cosolvents has been developed. Several cubic equations (EOS) and proper mixing rules are employed in correlating available experimental data of solubility ﬂ-carotene in supercritical CO2 involving polar cosolvents. The studies found that strong interaction in the system involving polar cosolvents occurred for which binary interaction parameters should be adjusted for correlating solubility of β-carotene. The strong interaction could be possibly that of solute-solute, solute- cosolvent or cosolvent association. The simple model, however, can predict solubility of β-carotene in that system studied after adjusting binary interaction parameters.